Carvacrol Essential Oil as a Neuroprotective Agent: A Review of the Study Designs and Recent Advances - Fahad Khan Tareen; Laura Catenacci; Sara Perteghella; Milena Sorrenti; Maria Cristina Bonferoni (Molecules)
Neurodegenerative diseases were mostly perceived as diseases of ageing populations, but now-a-days, these diseases pose a threat to populations of all age groups despite significant improvements in quality of life. Almost all essential oils (EOs) have been reported to have some neuroprotective abilities and have been used as supplements for good mental health over the centuries. This review highlights the therapeutic potential of one such monoterpene phenolic EO, carvacrol (CV), that has the potential to be used as a main therapeutic intervention for neurodegenerative disorders. Three libraries, Google Scholar, PubMed, and ScienceDirect, were explored for research studies related to the neuroprotective roles of CV. All the research articles from these libraries were sorted out, with the first article tracing back to 2009, and the latest article was published in 2024. The positive effects of CV in the treatment of Alzheimer’s and Parkinson’s Diseases, multiple sclerosis, ischemia, and behavioural disorders have been supported with evidence. This review not only focused on study designs and the pharmacological pathways taken by CV for neuroprotection but also focused on demographics, illustrating the trend of CV research studies in certain countries and the preferences for the use of in vitro or in vivo models in studies. Our review provides useful evidence about the neuroprotective potential of CV; however, a lack of studies was observed regarding CV encapsulation in proper dosage forms, in particular nanoparticles, which could be further explored for CV delivery to the central nervous system.